Utilizing Dipsticks to Measure Leukocyte Esterase in Urine to Detect UTIS - Kiran Memon, Shazia Ahmed Jatoi, Yasmeen Rasheed Bhutto, Abdul Saboor Soomro, Rukhsana Saboor, Durgha Devi, Aamir Ramzan, Kiran Aamir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The more expedient, less labor-intensive dipstick has come to be the tool of choice for diagnosing UTIs in the majority of primary care settings. The purpose of this study was to assess the usefulness of dipsticks in UTI diagnosis. Study Design: Descriptive study Place and Duration: Pathology Department Civil Hospital LUMHS. January 2021 to December 2021 Methods: Total 230 patients of both gender were presented in this study. The study included every urine sample that was received for urine culture by the Microbiology Department. The leukocyte esterase content of each specimen was measured using a urine dipstick. On Cysteine Lactose Electrolyte Deficient (CLED) agar, all of the urine samples were also used for culture. Every data was analysed using SPSS 24.0. Results: There were majority 125 (54.3%) females and 105 (45.7%) females among all cases. There were 75 (32.6%) LE positive and 120 (52.2%) were LE negative. Culture positive cases was 87 (37.8%) and 143 (62.2%) were culture negative. We found sensitivity (78.2%), specificity (86%), PPV (55.7%) and NPV (90.4%). The overall effectiveness of the LE Test with dipsticks was observed (84.3%). Conclusion: Under resource-constrained environments, the leukocyte esterase dipstick test is a quick and affordable screening method. Determining whether a urinary tract infection is present is very helpful. A negative test, however, gives a more accurate indication that a UTI is absent. Keywords: Urine culture, Urinary Tract Infection, Leukocyte esterase dipsticks